Practical Reforms in the Field of Copyright Protection in the Republic Of Uzbekistan and Their Promising Results - Ilyasov, Kakharman (Indonesian Journal Publisher, 2024)
This article examines the ongoing efforts to enhance legal literacy, awareness, and the protection of intellectual property rights in Uzbekistan, focusing on the “Strategy for the Development of Intellectual Property in the Republic of Uzbekistan for 2022-2026.” It highlights the significant legal reforms undertaken since the 2017-2021 development strategy, including the adoption of over a thousand laws aimed at fostering transparency, civil society engagement, and human rights protection. However, several challenges persist in the legal protection of intellectual property, such as inadequate public knowledge, weak integration of intellectual property in production processes, and insufficient coordination among relevant state bodies. The research explores how collective management of intellectual property rights, inspired by international models, can address these challenges. It also delves into the institutional reforms needed to ensure efficient legal protection, prevent counterfeit products, and promote the use of intellectual activity results in the economic and social sectors. The article concludes with recommendations for improving Uzbekistan’s intellectual property framework, increasing public engagement, and positioning intellectual property as a key driver of the country's socio-economic development.